THE EXPRESSION OF EMOTIONS THROUGH LANGUAGE - Zarnigor Ubaydullayeva (Scholars Digest Publishing, 2024)
This article examines the expression of emotions through language, which has been studied as a linguistic object since the second half of the twentieth century. It analyzes various theories and approaches aimed at identifying words with emotional load and their contextual significance. The article discusses factors influencing emotional interaction, the concept of "emotivity," and methods of expressing emotions. Additionally, it covers emotional metaphors, verbalization, and the communication process. The aim of the article is to delve deeper into the complex relationship between language and emotions.
Keywords: Emotions, Language, Emotivity, Verbalization, Metaphors, Psycholinguistics, Cognitive linguistics, Linguoculturology.